2021
DOI: 10.1029/2020ja028452
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Electrical Conductivity in the Topside Ionosphere Derived From Swarm Measurements

Abstract: Our knowledge of the physical properties of the topside ionosphere is still incomplete. A key point still not fully understood is how field‐aligned currents are generated, evolve and dissipate in the ionosphere. Answering to this question is fundamental for a better understanding of the mechanisms regulating the coupling between magnetosphere and ionosphere and to shed light on the physical processes inherent to space weather events occurring in the Earth's ionosphere. In this framework a relevant role is play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 97 publications
(180 reference statements)
1
16
0
Order By: Relevance
“…In fact, the characteristic shape of the magnetic equator and of the auroral regions stand out, and this is somewhat expected because the plasma in the topside ionosphere is generally constrained by the geomagnetic field [47]. This behavior has also been recently confirmed by Giannattasio et al [48,49] that, by using Swarm data, identified patterns in the parallel electrical conductivity (which is crucially affected by T e ) related to features of the geomagnetic field such as regions R1 and R2 [50] or the magnetic cusp [51]. They also identified variations in the parallel electrical conductivity due to MLT, QD latitude, season, solar, and geomagnetic activity.…”
Section: Statistical Trends Of Swarm-measured Electron Temperature Values and Comparison With Iri-modeled Onesmentioning
confidence: 67%
See 1 more Smart Citation
“…In fact, the characteristic shape of the magnetic equator and of the auroral regions stand out, and this is somewhat expected because the plasma in the topside ionosphere is generally constrained by the geomagnetic field [47]. This behavior has also been recently confirmed by Giannattasio et al [48,49] that, by using Swarm data, identified patterns in the parallel electrical conductivity (which is crucially affected by T e ) related to features of the geomagnetic field such as regions R1 and R2 [50] or the magnetic cusp [51]. They also identified variations in the parallel electrical conductivity due to MLT, QD latitude, season, solar, and geomagnetic activity.…”
Section: Statistical Trends Of Swarm-measured Electron Temperature Values and Comparison With Iri-modeled Onesmentioning
confidence: 67%
“…Therefore, in the absence of mechanisms that reduce the energy of precipitating particles T e is free to increase due, e.g., to energy exchanges with the nightside magnetosphere. Not surprisingly, there is an anticorrelation between N e and T e , and T e is significantly enhanced in regions of depleted N e , such as between region R2 and the main trough in the nightside winter; while, in contrast, it decreases in regions of enhanced N e due to energy loss to the ions [19,48,49,57,63]. Some studies in the past tried to establish a link between N e and T e , since N e is a major factor in electron energy loss due to the ionospheric plasma quasi-neutrality (density of ions is nearly equal to N e ).…”
Section: Statistical Trends Of Swarm-measured Electron Temperature Values and Comparison With Iri-modeled Onesmentioning
confidence: 96%
“…The sign-singularity analysis of FACs was performed by analyzing separately the Northern and Southern Hemisphere crossings to investigate if there was any significant difference on the scaling features in the two hemispheres. This was justified by the fact that there is much evidence for a north-south asymmetry in the processes taking place in the polar ionospheric region, which could be a consequence of the different topology of the geomagnetic field and the different insolation/seasonal conditions [44][45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…In a recent work, Giannattasio et al. (2021), hereafter Paper I, for the first time provided high‐resolution maps of electrical conductivity in the direction parallel to the main geomagnetic field in the ionospheric F layer by using in‐situ Swarm measurements. Compared to the work by Amm et al.…”
Section: Introductionmentioning
confidence: 99%
“…Amm et al (2015), for example, took advantage of electric and magnetic in-situ measurements from the Swarm mission (Friis-Christensen et al, 2006) flying in the F layer at ∼500 km of altitude to retrieve field-aligned, Hall, and Pedersen conductivity at ∼110 km of altitude. In a recent work, Giannattasio et al (2021), hereafter Paper I, for the first time provided high-resolution maps of electrical conductivity in the direction parallel to the main geomagnetic field in the ionospheric F layer by using in-situ Swarm measurements. Compared to the work by Amm et al (2015), we used only actual data measured by Langmuir probes to provide climatological maps at the flight altitude of Swarm A, without relying on models to extrapolate the behavior of the conductivity in the E layer.…”
mentioning
confidence: 99%